Imagery ability in Boccia: The effects of an intervention program - Amorim, André Jorge Pinto (2019)
Submitted by Pessoa (pfep@ubi.pt) on 2019-03-28T16:16:33Z No. of bitstreams: 1 tese_andre_amorim_finalissima (2).pdf: 755329 bytes, checksum: 13b1a3855add79563fee2a773ab021c6 (MD5)